Effectiveness Health Promotion Of Breast Examination Using Video Media On Knowledge About Breast Awareness Young Women At MA Syarief Hidayatullah Paiton Probolinggo - Listina Pricahyati; Amarin Yudhana (Indonesian Journal of Nutritional Epidemiology and Reproductive, 2022)
Breast cancer is a malignancy of breast tissue that can originate from the ductal or lobular epithelium. Cancer is the leading cause of death, accounting for 13% of all causes of death. The incidence of breast cancer from year to year is increasing. This is influenced by the low knowledge of adolescents. Analyzing the effectiveness of health promotion using video media to increase knowledge about BSE in adolescent girls at MA Syarief Hidayattullah. This study is a quantitative study using a quasi-experimental design with a white control group pre-test post-test. implemented as a measure of intervention. The subjects of this study were young women as many as 30 respondents, data analysis used the Wilcoxon test and the Mann Whitney test. The results of the analysis obtained a significant difference from the test results between the experimental group and the control group on the knowledge of young women about BSE. Which in the experimental group the p value 0.001 < (0.05) and the negative group with a p value of 0.257 > (0.05). And the statistic from the Mann test-significance p 0.000 < 0.05. This shows that there is a significant difference between the Experimental group and the control group on the knowledge of adolescent girls about BSE. There is a significant difference between the control group and the intervention group, which means that the promotion of BSE Health using video media is Effective to increase knowledge about BSE in adolescent girls in MA Syarief Hidayatullah Paiton-Probolinggo.